Semaphorin-3A inhibits multiple myeloma progression in a mouse model. (9th August 2018) - Lavi, Noa; Kessler, Ofra; Ziv, Keren; Nir-Zvi, Inbal; Mumblat, Yelena; Eiza, Nasrene; Paran, Yael; Brenner, Benjamin; Vadasz, Zahava; Neufeld, Gera
Abstract : We find that serum sema3A concentrations decrease in relation to tumor cell infiltration of the bone marrow in multiple myeloma (MM) and patients with leukemia, and that stabilized forms of sema3A can perhaps be used to inhibit MM progression. Abstract: Previous studies revealed that progression of multiple myeloma (MM) is associated with downregulation of semaphorin-3A (sema3A) expression in bone marrow endothelial cells. We therefore determined if serum sema3A concentrations are correlated with MM progression and if sema3A can affect MM progression. We find that the concentration of sema3A in sera of MM patients is strongly reduced and that the decrease is correlated with disease progression. A similar depletion is found in patients having acute myeloid leukemia and acute lymphoblastic leukemia but not in cancer forms that do not involve the bone marrow such as in colon cancer. Expression of a modified sema3A [furin-resistant sema3A (FR-sema3A)] stabilized against cleavage by furin-like proprotein convertases in CAG MM cells did not affect their behavior in-vitro . CAG cells injected into the tail vein of severe combined immunodeficient (SCID) mice home to the bone marrow and proliferate, mimicking MM disease progression. Disease progression in mice injected with CAG cells expressing FR-sema3A was inhibited, resulting in prolonged survival and a lower incidence of bone lesions. Histological examination and fluorescence-activated cell sorting analysis revealed that FR-sema3A expression reduced the infiltration of the CAG cells into the bone marrow, reduced bone marrow necrosis and reduced angiogenesis induced by the MM cells in the bone marrow. Our results suggest that measurement of sema3A serum concentrations may be of use for the diagnosis and for the monitoring of malignancies of the bone marrow such as MM. Furthermore, our results suggest that FR-sema3A may perhaps find use as an inhibitor of MM disease progression.